Usefulness of perampanel as initial monotherapy in children with non-lesional focal epilepsy - Hideaki Kanemura; Yoshihiro Miyasato; Yutaro Tomi; Fumikazu Sano (Epilepsy & Behavior Reports)
This study aimed to compare carbamazepine (CBZ) and perampanel (PER) in terms of the efficacy against clinical seizures and electroencephalographic abnormalities such as interictal epileptiform discharges (IEDs) and safety as initial monotherapy in children with non-lesional focal epilepsies. This retrospective review included participants recruited from among epilepsy outpatients treated at the authors’ hospital between January 01, 2000, and December 31, 2019 in the CBZ group and between January 01, 2020, and December 31, 2022 in the PER group. The inclusion criterion in both groups was ≥12 months of follow-up. Responders were identified as participants demonstrating complete disappearance (100 % reduction in seizures or IEDs) or response (>50 % reduction in seizure frequency or IEDs). Safety primary outcome was defined as appearance rate of AEs. The study group comprised 247 participants treated with CBZ and 46 participants treated with PER. Total efficacy rate for clinical seizures was significantly higher with PER than with CBZ (p = 0.0148). Moreover, the rate of complete disappearance was significantly higher with PER than with CBZ (p = 0.0133). Total efficacy rate for IED was again significantly higher with PER than with CBZ (p < 0.0001). The appearance of adverse events was significantly lower with PER than with CBZ (p = 0.023). PER may be useful as initial monotherapy in children with non-lesional focal epilepsies.